2008
DOI: 10.1016/j.jasms.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of substituted-benzene dopants for charge exchange ionization of nonpolar compounds by atmospheric pressure photoionization

Abstract: Atmospheric pressure photoionization (APPI) using a dopant enables both polar and nonpolar compounds to be analyzed by LC/MS. To date, the charge exchange ionization pathway utilized for nonpolar compounds has only been efficient under restrictive conditions, mainly because the usual charge exchange reagent ions-the dopant photoions themselves-tend to be consumed in proton transfer reactions with solvent and/ or dopant neutrals. This research aims to elucidate the factors affecting the reactivities of substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…In DA-APPI, the chlorobenzene radical cation appeared as the most abundant solvent ion at 0.05 and 0.1 mL/ min flow rate, but an ion at m/z 108 was the most prominent at higher flow rates. Robb et al have also reported the m/z 108 reagent ion for chlorobenzene in DA-APPI-MS under slightly different experimental conditions [12]. Here, in DA-APPI, the MS/MS measurement showed that the fragmentation of the m/z 108 ion is identical to that of M +.…”
Section: Reagent Ionsmentioning
confidence: 54%
See 4 more Smart Citations
“…In DA-APPI, the chlorobenzene radical cation appeared as the most abundant solvent ion at 0.05 and 0.1 mL/ min flow rate, but an ion at m/z 108 was the most prominent at higher flow rates. Robb et al have also reported the m/z 108 reagent ion for chlorobenzene in DA-APPI-MS under slightly different experimental conditions [12]. Here, in DA-APPI, the MS/MS measurement showed that the fragmentation of the m/z 108 ion is identical to that of M +.…”
Section: Reagent Ionsmentioning
confidence: 54%
“…Robb et al [12] previously suggested that in DA-APPI the m/z 108 ion (anisole) is formed in a substitution reaction between neutral methanol and chlorobenzene radical cation following a general reaction scheme for several halobenzenes:…”
Section: Comparison Of Charge Exchangementioning
confidence: 99%
See 3 more Smart Citations